Plasmonic Hot Electron Induced Structural Phase Transition in a MoS2 Monolayer. (7th August 2014) - Kang, Yimin; Najmaei, Sina; Liu, Zheng; Bao, Yanjun; Wang, Yumin; Zhu, Xing; Halas, Naomi J.; Nordlander, Peter; Ajayan, Pulickel M.; Lou, Jun; Fang, Zheyu
<x xml:space="preserve">Abstract</x> A reversible 2H‐to‐1T phase transition in a MoS2 monolayer is realized by plasmonic hot electrons. This transition can be actively controlled by the incident light intensity, wavelength, sample areas, and perimeters, resulting in an effective shift of photoluminescence. The suggested configuration paves the way for plasmonic optoelectronic device applications of MoS2 in the future. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>